Дослідження на території замку Хотинської фортеці - Мисько, Ю.В.; Пивоваров, С.В. (Археологічні дослідження в Україні, 2010)
The paper concerns the research on the territory of the inner yard of a castle in Khotyn fortress. It was ascertained that after rebuilding in the beginning of the 18th c. the entrance tower which was known from the pictures of the Western European artists had been destroyed. The base of the tower was excavated, the thickness of its walls was determined, and the material which allows the authors to determine the time of construction and destruction of the tower was obtained.